Management in Descemet’s membrane detachment after cataract surgery – case report - Wylęgała, Edward; Nowińska, Anna; Dobrowolski, Dariusz; Wróblewska-Czajka, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Descemet’s membrane detachment (DMD) is a rare, but serious complication of cataract surgery. It can cause permanent corneal edema that results in severe visual loss. Small detachments resolve with topical medical therapy within few weeks to few months. Larger detachments usually require surgical intervention. We present a case report of a patient with Descemet’s membrane detachment that occurred one day after complicated phacoemulsification cataract surgery. At 3 months after surgery visual acuity was 3/50 and persistent corneal edema was observed. Anterior chamber tamponade with air under topical anesthesia successfully reattached Descement’s membrane. The corneal edema regressed and the gas bubble resolved by the fifth day after surgery. Patient’s left visual acuity was 5/12. The intraocluar pressure was 17 mmHg. We believe this method is safe, effective and results in fast visual acuity improvement.